Implementation of Fulfilling The Constitutional Rights of Citizens in Religion: Case Study of Batur Village, Indonesia - Cholida Hanum (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
In recent years, various events showing the existence of religious freedom have become a phenomenon. Violation of respect for the individual’s freedom to embrace and practice religious freedom has an impact on all aspects of life, including education, health, employment, and access to public services. As the national organizer, the government plays an important role in creating a favorable, safe and peaceful atmosphere for the people. The slogan of Bhinneka Tunggal Ika seems to be only utopian, which is reflected in the civil relations in the village of Batur, where occupations are multi-religious. But it is important to note that the term "villages of tolerance" is not only symbolic. Studies have shown that the rights stipulated by the constitution are mentioned as village tolerance rights, and the extent to which these rights are realized in the future should be fully supported by the local government and the village government. The research is qualitative, collecting primary data through interviews and secondary data through documents related to the problem. The result of this research is that the realization of the religious rights of Semarang Regent in Batur Village is not top-down (from the state to the citizens), it is precisely that the realization of religious rights in Batur Village is collectively discussed. The community’s own awareness and mutual encouragement to create a harmonious and coordinated shared life between one religion and another